Boosting Students’ Speaking Skill Through Information Gap Activities (IGA) - Mahmudah, Listiana Eka Dewi; Anggreni, Afrillia; Dewi, Anjar Kusuma; Marhum, Mochtar (Journal of English Language and Education, 2025)
Speaking proficiency is essential for academic and social development of EFL students. However, numerous students often struggle with limited vocabulary, grammatical deficiencies, and a lack of confidence which contribute to their speaking performance. Therefore, this study exposes the effectiveness of Information Gap Activities (IGA) to elevate students’ speaking skills – specifically in fluency and comprehensibility – of eleventh-grade students at SMA Negeri 1 Sigi. A quasi-experimental design was employed, involving two groups: an experimental class received IGA treatment and a control class taught by using conventional methods, with a total of 60 student participants. Both groups were given pre-tests and post-tests to measure their speaking ability before and after the treatment. Pre-test and post-test data were analyzed using SPSS. The results revealed a statistically significant improvement in the experimental group, with the mean score increasing from 41.67 to 67.50, compared to the control group’s increase from 41.67 to 50.56. The Wilcoxon Signed-Rank Test (p = 0.000) and Mann-Whitney U Test (p = 0.000) confirmed this difference to be statistically significant. These findings suggest that Information Gap Activities can effectively enhance students’ speaking abilities, offering a communicative and interactive alternative to traditional instructional approaches.